2015
DOI: 10.1248/bpb.b15-00124
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Tricaprylin Emulsion on Anti-glomerular Basement Membrane Glomerulonephritis in Rats: <i>In Vivo</i> and <i>in Silico</i> Studies

Abstract: Glomerulonephritis (GN) is a set of pathological conditions that result in the destruction of glomeruli and loss of renal function, commonly leading to the development of end-stage renal disease. Current pharmacotherapy is limited to immunosuppressive therapy. In the present study, we found a novel antinephritic effect of a tricaprylin emulsion in the anti-glomerular basement membrane (anti-GBM) GN rat model. We evaluated the treatment in vivo by comparing administration of the emulsion with administration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Although various studies have used microarray analyses so far, it is not easy to extract biological meanings from the analyses. In this study, we applied the previously-established GO-based microarray analysis [25] to the present study, and successfully found that IHT and aging shared alterations in some common GO, which were also observed with kainic acid treatment, Dicer ablation, or moderate glutamate excess. By performing in vivo analyses, we found that IHT increased P-tau via at least activation of mTOR signaling pathway, and decreased levels of postsynaptic proteins.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Although various studies have used microarray analyses so far, it is not easy to extract biological meanings from the analyses. In this study, we applied the previously-established GO-based microarray analysis [25] to the present study, and successfully found that IHT and aging shared alterations in some common GO, which were also observed with kainic acid treatment, Dicer ablation, or moderate glutamate excess. By performing in vivo analyses, we found that IHT increased P-tau via at least activation of mTOR signaling pathway, and decreased levels of postsynaptic proteins.…”
Section: Discussionmentioning
confidence: 90%
“…were examined and visualized using R/Bioconductor [28], as described previously [25, 28]. The expression levels of our microarray data were calculated from probe intensities and arrays normalized using the mas5 method [29].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, in our another study, we have provided a mechanistic clue for the understanding of experimental crescentic GN and the pharmacological effects of a CK2 inhibitor and other treatment by microarray analysis. 22) The results provided further insight on the possible relationship between GN and CK2. To develop CK2 inhibitors as therapeutic agents for GN, Fuchi et al had synthesized compound 13 based on the structure of 2,6-disubstituted pyrazines.…”
Section: Discussionmentioning
confidence: 76%
“…At first, we performed Gene Ontology (GO)-based microarray analyses that was previously established by Dr. Hirasawa and his colleagues [3]. We included data derived from mice reared for 12 months (referred to “aging”).…”
mentioning
confidence: 99%